Trends in Summer Season Climate for Eastern Europe and Southern Russia in the Early 21st Century - Maria G. Lebedeva; Olga V. Krymskaya; Anthony R. Lupo; Yury G. Chendev; Alexandr N. Petin; Alexandr B. Solovyov (Advances in Meteorology)
The goal of this research is to evaluate changes in temperature and precipitation in the Central Chernozem Region of southwestern Russia during the summer and relate these to large-scale circulation types and synoptic circulation processes. Some of these circulation regimes result in extreme weather conditions over the region. Using a classification system for Northern Hemisphere large-scale flow regimes and observations of weather within the Central Chernozem Region, the role of individual synoptic patterns in the formation of weather anomalies was identified. Also, comparing the periods 1981–2010 and 1971–2000, the mean summer temperatures increased by 0.6°C regionally. During the most recent decade the increase was 1.3°C. Total precipitation for the summer increased over the 20th century and was characterized by less variability during the second half when compared to the first half. However, in the beginning of the 21st century, precipitation has decreased during the growing season, but variability has increased. The increase in summer temperatures and increased variability in precipitation were then linked to an increase in the occurrence of weather regimes associated with warm anomalies and blocking. Finally, the results of this study can be used to translate larger-scale seasonal or climate forecasts to the regional scale.